Racial differences in presentations and predictors of acute pain after motor vehicle collision. Issue 6 (June 2018) - Beaudoin, Francesca L.; Gutman, Roee; Zhai, Wanting; Merchant, Roland C.; Clark, Melissa A.; Bollen, Kenneth A.; Hendry, Phyllis; Kurz, Michael C.; Lewandowski, Christopher; Pearson, Claire; O'Neil, Brian; Datner, Elizabeth; et al.
Abstract : Abstract: African Americans experience a greater burden of acute pain than non-Hispanic white individuals across of variety of acute medical conditions, but it is unknown whether this is the case after trauma. We evaluated pain, pain-related characteristics (eg, peritraumatic distress), and analgesic treatment in 2 cohorts of individuals (African American [n = 931] and non-Hispanic white [n = 948]) presenting to the emergency department (ED) after a motor vehicle collision. We performed a propensity-matched analysis (n = 796 in each group) to assess racial differences in acute pain in the ED. In multivariable models conducted within the matched sample, race was associated with moderate to severe axial pain (odds ratio [OR] 3.2; 95% confidence interval [CI]: 2.1-5.0, P < 0.001) and higher average numerical rating scale scores (1.3; 95% CI: 1.1-1.6; P < 0.001). After adjustment for pain and other covariates, non-Hispanic white patients were more likely to receive an opioid analgesic in the ED (OR 2.0; 95% CI: 1.4-3.0, P < 0.001) or at discharge (OR 4.9; 95% CI: 3.4-7.1, P < 0.001) and also less likely to receive an NSAID in the ED (OR 0.54; 95% CI: 0.38-0.78; P = 0.001) or at discharge (0.31; 95% CI: 0.43-0.84). Racial differences in the severity of acute posttraumatic pain after a motor vehicle collision are not explained by factors such as socioeconomic status or crash characteristics. Despite a higher burden of acute pain, African Americans were less likely to receive opioid analgesics and more likely to receive NSAIDs. Further work is needed to understand the relationship between pain severity, disparities in analgesic treatment, and longer term outcomes, such as post–motor vehicle collision chronic pain. Abstract : There are racial differences in acute pain after a motor vehicle collision, which are not explained by factors such as socioeconomic status or crash characteristics.